Comportamento e resistência de uma viga mista de aço e concreto em perfil formado a frio em temperatura elevada de uma edificação de baixo custo - Marcio Wanderson Rodrigues (2007)
In Brazil, one of the main problems to be solved by the society is the housing deficit, that now a day is around 7.9 million houses. A preeminent solution for this question is the creation of social programs that proposes the construction of low cost housing. In the case of low cost housing, for example, the houses must have their cost reduced to amaximum, without compromising its safety and functionality, and its large scale production must be done easily. With this, all the technical solutions known by the engineering must be applied in order to rationalize the projects more each time. One of the analyses that can be done to reduce the use of steel in the structures is the study of the contribution of the concrete floor in the beams resistance. In this assignment a study related to the dimension of a high temperature mixed steel beam and a cold formed steel of a low cost apartment, projected following the constructive system desenvolved by UFMG with a technological partnership with Usiminas. It's described and molded thisbeam's behavior undergone natural fire. The resistance of this mixed steel beam in high temperature was determined by simplified method of the brazilian regulation ABNT NBR 14323: 1999. The CFD model of the fire scenario was done with the SMARTFIRE software. The thermal analysis of the mixed structure in high temperature was done with the THERSYS software, and the structural analysis was done with theVULCAN software. Taking in consideration all the possibilities in the advanced analysis, it was concluded that the strength of the beam analyzed at high temperature was reached in 13 min, and that it has acceptable levels of safety.